2022
DOI: 10.1186/s12885-022-09328-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and immune relevancy of a combined autophagy-, apoptosis- and necrosis-related gene signature in glioblastoma

Abstract: Background Glioblastoma (GBM) is considered the most malignant and devastating intracranial tumor without effective treatment. Autophagy, apoptosis, and necrosis, three classically known cell death pathways, can provide novel clinical and immunological insights, which may assist in designing personalized therapeutics. In this study, we developed and validated an effective signature based on autophagy-, apoptosis- and necrosis-related genes for prognostic implications in GBM patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 116 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…In this study, the results of these two analyses showed significant differences in different risk score subgroups (Supplementary Figure S6A-E), further supporting the feasibility of the risk score model to be used for the clinical prognostic assessment. Subsequent immune checkpoint analyses revealed that the expressions of CD274, CTLA4, PDCD1, and LAG3 in the high-risk group were significantly higher than those of the low-risk group, suggesting that the high expression of related genes might be one of the reasons that affected GBM treatment and prognosis (Supplementary Figure 6F-I), which was also consistent with previous reports on the correlation between those four genes and the glioblastoma prognosis (Andrews et al, 2020;Du et al, 2020;Yang et al, 2021;Bi et al, 2022;Preddy et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the results of these two analyses showed significant differences in different risk score subgroups (Supplementary Figure S6A-E), further supporting the feasibility of the risk score model to be used for the clinical prognostic assessment. Subsequent immune checkpoint analyses revealed that the expressions of CD274, CTLA4, PDCD1, and LAG3 in the high-risk group were significantly higher than those of the low-risk group, suggesting that the high expression of related genes might be one of the reasons that affected GBM treatment and prognosis (Supplementary Figure 6F-I), which was also consistent with previous reports on the correlation between those four genes and the glioblastoma prognosis (Andrews et al, 2020;Du et al, 2020;Yang et al, 2021;Bi et al, 2022;Preddy et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, the establishment of diagnosis or prognosis models from the particular aspect of biological processes, such as ferroptosis, 45,46 necrosis, 47 lipid metabolism, 48,49 and acetylation, 50 and the tumor immune microenvironment, 51,52 has attracted increasing interest.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while the control sphere, U87MG, revealed Ki-67 positivity of about 40%, the neutrophil groups, in both initial and advanced tumor 3D models, reached a plateau of about 80%, demonstrating that growth was significantly higher when there is crosstalk between these cells. Necrosis is a relevant finding in clinical tumor samples, being an indication of malignancy ( 35 ). Thus, since our experiments revealed increased levels of necrosis in the presence of neutrophils, it is suggested that neutrophils could help in inducing necrosis within the tumor niche, favoring the poor prognosis in glioma patients.…”
Section: Discussionmentioning
confidence: 99%